Pre-emptive horizontal mergers: theory and evidence - József Molnár (Bank of Finland, 2007)
This paper proposes and tests an explanation as to why rational managers seeking to maximize shareholder value can pursue value-decreasing mergers. It can be optimal to overpay for a target firm and decrease shareholder value if the loss is less than in an alternative where the merger is undertaken by a product market rival. This paper presents a model based on synergies, market power and competition for merger targets. Consistent with the model the empirical results obtained here show a strong correlation between the returns of acquiring firms and close rivals around merger events.
URN:NBN:fi:bof-20140807540
Keywords: G34; G14; D43; D44; L13; 330; acquisitions; auction; event study; oligopoly; preemption